Synthesis, spectral investigation, biological efficacy, and computational evaluation of the hydroxamic acid chelator and its Zn(II) metal complex with potent anticancer activity - Sharma, Shubham; Thakur, Maridula; Sharma, Sohini; Kanwar, Shamsher Singh; Kumari, Meena (European Journal of Chemistry, 2024)
The biologically active Zn(II) complex [Zn(HL)2] (HL = 3-OCH3C6H4-(CO)NHO) has been synthesized by the reaction of ZnSO4 with potassium 3-methoxybenzohydroxamate (KHL, 3-OCH3C6H4CONHOK) in a 1:2 molar ratio in MeOH solvent medium simply stirring, avoiding drastic conditions and hazardous chemicals. Physicochemical (elemental analysis, molar conductivity) and spectroscopic studies (FTIR, UV-visible, 1H NMR, and 13C NMR) were conducted to characterize the complex. The coordination involving the oxygen atoms of carbonyl and hydroxamic groups (O,O coordination) and the presence of a distorted tetrahedral geometry around the complex have been inferred on the basis of computational studies. Computational investigations indicate that the complex exhibits greater stability in comparison to that of the ligand, and additional calculations were conducted to assess various chemical reactivity parameters. The biological efficacy of the complex has been evaluated through investigations of its antimicrobial, cytotoxic, and anticancer properties, complemented by DNA binding and docking analyzes. The antimicrobial activity of the ligand and the complex against selected bacteria (S. aureus, S. typhi, E. coli, S. flexneri) and fungi (R. solani, A. alternata, and F. sambucinum) was also evaluated. The complex was found to be more toxic against the bacterial species S. typhi and E. coli and showed efficient inhibitory activity against the fungi F. sambucinum and A. alternata. The results were compared with the standard antibacterial drug tetracycline and the antifungal drug amphotericin B. In vitro cytotoxicity assessments were performed using L20B cell lines, which are malignant mouse cells expressing the human poliovirus receptor (CD155), and Rhabdomyosarcoma RD cancer cell lines derived from muscle tissue. The findings revealed decreased cell viability, which is correlated with the increase in the concentrations of the test compounds, demonstrating potent anticancer activity specifically against rhabdomyosarcoma cancer cell lines. Additionally, molecular docking investigations were performed to explore the molecular interactions between the ligand, the complex, and the crystal structure of the A. alternata allergen (3V0R), further supporting the efficacy of both the ligand and the complex.